Early Modern Social Networks: Antecedents, Opportunities, and Challenges. Issue 2 (2nd April 2019) - Davison, Kate
Abstract: This article reflects on the rising use of concepts, theories, and methodologies taken from social network analysis in early modern history, along with the opportunities and challenges it presents. Scholars have been quick to attribute the growing interest in historical social networks to movements for interdisciplinary research, new possibilities presented by digital technologies, and the prominence of the term "social network" in present-day culture. In contrast, this article reconnects recent trends to longstanding attention to the nature of early modern social relations, which has its roots in the foundations of modern social thought laid in the nineteenth and early twentieth centuries, and developed through the postwar decades in both history and sociology. In doing so, the article shows the extent to which social network analysis shares antecedents, interests, and goals with more traditional historical methods. It argues that, when sensitively applied, network approaches present many opportunities for historians engaging with enduring questions about the nature of social relations in the past.